Isolation and characterisation of sesquiterpene synthase from aromatic orchid Phalaenopsis bellina (Rchb.f.) Christenson - Ahmad Asnawi Mus; Jualang Azlan Gansau; Vijay Kumar Subbiah; Nor Azizun Rusdi (Springer Netherlands, 2024)
Background Phalaenopsis bellina, an orchid native to Borneo, is renowned for its unique appearance. It releases distinct fragrances, which have been linked to the presence of terpenoids. However, the identifcation and study of sesquiterpene synthase in P. bellina remain limited. In this study, we examines the functional characterisation of terpene synthase (TPS) from P. bellina, known as PbTS, through recombinant protein expression and its manifestation in the fower. Methods and Results Gene annotation of PbTS revealed that the inferred peptide sequence of PbTS comprises 1,680 bp nucleotides encoding 559 amino acids with an estimated molecular mass of 65.2 kDa and a pI value of 5.4. A similarity search against GenBank showed that PbTS shares similarities with the previously published partial sequence of P. bellina (ABW98504.1) and Phalaenopsis equestris (XP_020597359.1 and ABW98503.1). Intriguingly, the phylogenetic analysis places the PbTS gene within the TPS-a group. In silico analysis of PbTS demonstrated stable interactions with farnesyl pyrophosphate (FPP), geranyl pyrophosphate (GPP), and geranylgeranyl pyrophosphate (GGPP). To verify this activity, an in vitro enzyme assay was performed on the PbTS recombinant protein, which successfully converted FPP, GPP, and GGPP into acyclic sesquiterpene β-farnesene, yielding approximately 0.03 mg/L. Expressional analysis revealed that the PbTS transcript was highly expressed in P. bellina, but its level did not correlate with β-farnesene levels across various fowering time points and stages. Conclusion The insights gained from this study will enhance the understanding of terpenoid production in P. bellina and aid in the discovery of novel fragrance-related genes in other orchid species.